Co-activation of jaw and neck muscles during submaximum clenching in the supine position - Giannakopoulos, Nikolaos Nikitas; Schindler, Hans J.; Rammelsberg, Peter; Eberhard, Lydia; Schmitter, Marc; Hellmann, Daniel (Archives of oral biology, 2013)
Objective - The purpose of this study was to test the hypothesis that jaw clenching induces co-contraction and low-level long-lasting tonic activation (LLTA) of neck muscles in the supine position. - Design - Ten healthy subjects developed various feedback-controlled submaximum bite forces in different bite-force directions in supine position. The electromyographic (EMG) activity of the semispinalis capitis, semispinalis cervicis, multifidi, splenius capitis, levator scapulae, trapezius, sternocleidomastoideus, masseter and infra/supra-hyoidal muscles was recorded. For normalization of EMG data, maximum-effort tasks of the neck muscles were performed. - Results - Co-contractions of the posterior neck muscles varied between 2% and 11% of their maximum voluntary contraction. Different bite forces and bite-force directions resulted in significant (p<.05) activity differences between the co-contraction levels of the neck muscles. In addition, LLTA of specific neck muscles, provoked by the jaw clenching tasks, was observed. - Conclusions - This study demonstrated for the first time moderate co-contractions of jaw and neck muscles in the supine position under controlled submaximum jaw clenching forces. LLTA of most neck muscles was observed, outlasting clenching episodes and indicating an additional neuromuscular interaction between the two muscle groups.